Beyond Scheherazade: the re-emergence of the female Arab literary voice through multiple forums - Alghamdi, Alaa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Arab women have had a long history of participation in literary life, particularly in the community oriented, interactive literary salons that have existed since pre-Islamic times . The inherent message of such forums has always been, and continues to be, that literature is for sharing .
Keywords: Scheherazade; Arab women; voice; female writers; social systems